The Effect of Celebrity endorsers and Brand image on Purchasing Decisions for MakeOver Cosmetic Products in Bandar Lampung - Briggite Loren Panggabean; Dora Rinova (Cita konsultindo, 2024)
This study aims to investigate the influence of celebrity endorsers as well as brand image on purchasing decisions for Makeover cosmetic products in Bandar Lampung. Celebrity endorsers as well as brand image have been recognized as important factors in shaping customer preferences as well as influencing purchase decisions. This research was conducted to gain deeper knowledge about how these two factors influence consumer behavior in the cosmetics market. The research method used a survey through a questionnaire distributed to 200 respondents in Bandar Lampung who are users of Makeover cosmetic products. The data analysis technique used multiple regression to test the relationship between celebrity endorsers, brand image, as well as purchasing decisions. The results showed that celebrity endorsers as well as brand image have a significant positive influence on purchasing decisions for Makeover cosmetic products. This shows that the presence of celebrity endorsers as well as a strong brand image is able to influence customer perceptions as well as increase their interest in buying these products.